2016
DOI: 10.1111/codi.13316
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the accuracy of computed tomography colonography when defining anatomy for novel full‐thickness colonic excision techniques in early colonic neoplasia

Abstract: CTC can accurately assess the key morphological features for the selection of patients with early colonic neoplasia for full-thickness laparo-endoscopic excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…If the lesion is located at mesenteric side or involves more than half of the circumference of colonic wall, it is considered not suitable for FLEX due to risks of bleeding, ischemia and post-operative stricture. Currie et al (29,46) suggested computed tomography colonography (CTC) should be done to select patients for FLEX. In their study, CTC correctly identified the location of the lesions in relation to the mesenteric border in all patients.…”
Section: Flexmentioning
confidence: 99%
“…If the lesion is located at mesenteric side or involves more than half of the circumference of colonic wall, it is considered not suitable for FLEX due to risks of bleeding, ischemia and post-operative stricture. Currie et al (29,46) suggested computed tomography colonography (CTC) should be done to select patients for FLEX. In their study, CTC correctly identified the location of the lesions in relation to the mesenteric border in all patients.…”
Section: Flexmentioning
confidence: 99%
“…8 Furthermore, it has been found to be accurate with regard to finely targeted interventions of the solid abdominal viscera 9 and more recently, the colon itself. 10 Is this anatomical difference important?…”
Section: Is Ct a Suitable Technique To Analyse This Anatomy?mentioning
confidence: 99%
“…Patients were reviewed using endoscopy, and the Paris Classification of the polyp was recorded. All patients considered for FLEX underwent a CT colonography (CTC) to define the location of the polyp, mesenteric relationship and proportion of bowel circumference involvement, as previously described . The CTC images were then reviewed using the overview and endoluminal and cross‐sectional views in order to plan and rehearse the surgery (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The median (IQR) polyp diameter in the benign polyps was 35 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) mm. The median specimen diameter for completed FLEX procedures was 53 (48.5-60) mm (Table 2) (Fig.…”
Section: Treatment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation